(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The goal of the study is to find out how consumers think about FinTech and what factorsinfluence their adoption of the technology. FinTech is a new industry that uses technology to helppeople manage their money better.Fintech, or financial technology, is a term used to describe anytechnology that provides financial services through software, such as online banking, mobile paymentapplications or evenelectronic money. It is a broad category that includes many different technologies,but the main aim is to change the way consumers and businesses access their finance and compete withtraditional financial services. For instance, phone pay, Bharatpays, google pay, amazon pay, NEFT, etc.The data was collected from 166 respondents in Pune region using the structured questionnaire todetermine customer preferences.According to the report, more consumers use digital payment servicessince they reduce the danger of cash theft and also it makes money available to customers whenever itneeded i.e., easyaccessibility of their money, save‟s time. This changed the customers attitude andadoption towards Fintech Industry.